Pengaruh Terpaan Media Massa Online Terhadap Perilaku Konsumtif dan Dampaknya Terhadap Psikologi Generasi Z - Kya Dewi Davina; Davina Keisha Salsabila; Siti Nurhaliza Safitri; Kholis Ridho (Universitas Lambung Mangkurat, 2025)
Online mass media is growing rapidly over time, especially among Generation Z. Not only a tool for finding information or exchanging messages, online mass media can also be used as a place of transaction. The ease of accessing product information on online mass media triggers an increase in the buying and selling process, resulting in lifestyle changes that lead to consumptive behavior. The purpose of this study is to determine the influence, factors, and psychological impact of online mass media exposure on changes in the consumptive behavior of generation Z. The approach taken is a descriptive quantitative method with a quantitative approach. The approach taken was a descriptive quantitative method with a questionnaire as a research instrument. The population taken is people who belong to generation Z. The results of the study show that the influence of online mass media exposure on the consumptive behavior of generation Z shows significant variations. As many as 50% of respondents were strongly influenced by online mass media exposure and behaved consumptive, 37% were moderately affected but did not show consumptive behavior, while 13% were not affected and remained rational in making purchasing decisions.